(untitled) (Salud, Arte y Cuidado, 2018)
The purpose of this study was to determine the symptomatology and depression levels of parents whose children were admitted to the Polyvalent Intensive Care Unit of Pediatric Teaching Hospital, in Barquisimeto, a city of the State of Lara. The investigation was framed in the positivist paradigm with a quantitative approach. It is a descriptive non-experimental transversal field design. The population was made up of 21 parents whose children were admitted to the ICU. The "Beck Depression Inventory" was applied to this population, previous informed consent. For the processing of the data, the descriptive statistics were used and the results were presented in tables and graphs. Conclusion: Parents whose children were admitted to the ICU present depressive symptoms at various levels. Because of this, they become a vulnerable population around this pathology